Pengembangan Desain Kemasan Produk Bumbu Pecel KWT Kenanga, Ngestiharjo, Daerah Istimewa Yogyakarta - Kalifatullah Ermaya, Sir; Nur Laela Ermaya, Husnah; Muchran, dkk, Murniady (LPPM Universitas Koperasi Indonesia, 2024)
We carried out this Community Service Activity (PKM) for the Women Farmers Group (KWT)